Nutritional Quality and Organoleptic Acceptability of Sorghum Based Complementary Food Mix for Infants and Children: NUTRITIONAL QUALITY AND ORGANOLEPTIC ACCEPTABILITY OF SORGHUM PRODUCTS - Sati, Vandana; Singh, Vishakha (Annals of Arid Zone, 2024)
Sorghum is one of the most important millet in the world but is under privileged despite of its nutritional and commercial advantages. Its use for infant foods needs to be popularized by applying several processing techniques and improving its nutritive value and thus formulating a home-based complementary food mix. Present study was conducted to design complementary food mix based on sorghum using malting and was analyzed for its chemical, physico-chemical, microbiological and sensory qualities using standard methods. Moisture, total ash, crude protein, crude fat, crude fibre, carbohydrate and energy content was found 2.21%, 2.26%, 14.0%, 3.74%, 0.35 %, 77.99% and 401.03 kcal, respectively. The values of physico-chemical properties such as water absorption capacity 166.26%, bulk density 0.64gml-1, water solubility index 46.66, swelling index 1.38 and viscosity 9.82cps were found. On the basis of microbial analysis, it was found that the complementary food mix was microbiologically safe for consumption by young children. Organoleptic evaluation revealed that the formulated mix was “liked very much” by the panel of judges. Based on the results, it is concluded that the formulated complementary food mix was nutritionally sound and is recommended for use as a complementary food for young children (6-24 months). The formulated complementary food mix may contribute in meeting the nutritional needs of children developing countries like India and alleviating malnutrition.